EFFICACY OF AYURVEDIC THERAPIES ON PSORIASIS: A REVIEW ON RESEARCHES CONDUCTED AT GUJARAT AYURVED UNIVERSITY, JAMNAGAR - Agrawal, Sandeep; Sharma, Rohit; Bedarkar, Prashant; Prajapati, PK (International Journal of Ayurveda and Pharma Research, 2015)
Psoriasis is a chronic disease that has substantial psychological and social impact on a patients life. However the treatment options available in contemporary system of medicine are not much satisfactory. Psoriasis is far more than just a skin disease and is equated to Eka Kushtha in Ayurveda. Various clinical studies have been carried out at different research centers in India on Psoriasis (Eka Kushtha). Present study is aimed to compile such available research works in various departments of two PG institutes under Gujarat Ayurved University. Total 27 completed research works on Psoriasis were found at PG (24) and PhD (3) levels, which revalidated the impact of various Ayurvedic treatment modalities (viz. Shodhana and Shamana). In Shamana therapy maximum drugs were of Vata Kapha Shamaka, Rakta Prasadana, Vishaghna, Kushthaghna and Kandughna etc. properties, which effectively counteract the etio-pathogenesis of Psoriasis. Whereas, in Shodhana therapy maximum times Virechana procedure was carried out. The therapies were found to be significantly effective and clinically safe as no adverse drug reactions were reported during treatment period.